2014
DOI: 10.1093/deafed/enu007
|View full text |Cite
|
Sign up to set email alerts
|

Sign Vocabulary in Deaf Toddlers Exposed to Sign Language Since Birth

Abstract: Lexical comprehension and production is directly evaluated for the first time in deaf signing children below the age of 3 years. A Picture Naming Task was administered to 8 deaf signing toddlers (aged 2-3 years) who were exposed to Sign Language since birth. Results were compared with data of hearing speaking controls. In both deaf and hearing children, comprehension was significantly higher than production. The deaf group provided a significantly lower number of correct responses in production than did the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Crucially, if modification of iconic signs bootstraps referential mapping, this differential pattern of results suggests different rates of acquisition in children. As such, our results are consistent with previous research that has shown that children learning a sign language acquire a greater proportion of predicates (than nominals) early on compared to children learning a spoken language (for whom the pattern is reversed) (Anderson & Reilly, , for American Sign Language (ASL); Hoiting, , for Sign Language of the Netherlands (NGT); Rinaldi, Caselli, Di Renzo, Gulli, & Volterra, , for Italian Sign Language (LIS).…”
Section: Discussionsupporting
confidence: 91%
“…Crucially, if modification of iconic signs bootstraps referential mapping, this differential pattern of results suggests different rates of acquisition in children. As such, our results are consistent with previous research that has shown that children learning a sign language acquire a greater proportion of predicates (than nominals) early on compared to children learning a spoken language (for whom the pattern is reversed) (Anderson & Reilly, , for American Sign Language (ASL); Hoiting, , for Sign Language of the Netherlands (NGT); Rinaldi, Caselli, Di Renzo, Gulli, & Volterra, , for Italian Sign Language (LIS).…”
Section: Discussionsupporting
confidence: 91%
“…By age five, hearing children essentially master the sound system and grammar of their language and acquire a vocabulary of thousands of words. Rinaldi et al [30] found similar patterns of vocabulary acquisition in the deaf children of deaf signing parents.…”
Section: Language Development In Generalmentioning
confidence: 80%
“…(). Children acquiring LIS also acquire signs for action earlier than for objects (Rinaldi, Caselli, Di Renzo, Gulli, & Volterra, ). Children acquiring Turkish Sign Language are more likely to use signs depicting action than those depicting perceptual features of objects (Ortega, Sümer, & Özyürek, ).…”
Section: Discussionmentioning
confidence: 99%